2021
DOI: 10.21037/atm-20-8037
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors associated with the clinical outcome of intertrochanteric hip fracture in high-risk elderly patients treated with total hip arthroplasty versus percutaneous external fixation

Abstract: Background: Little is known regarding the survival and functional recovery of elderly intertrochanteric hip fracture (IHF) patients after total hip arthroplasty (THA) versus percutaneous external fixation (PEF).This study aims to analyze the prognostic factors of THA and PEF in elderly IHF patients.Methods: A total of 155 consecutive elderly patients (mean age of 80 years) diagnosed with IHF were retrospectively reviewed from our database between January 1, 2010, and December 31, 2018. The preoperative, intrao… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…[11][12][13] These studies have demonstrated that being >60 years of age is a significant factor independently associated with higher mortality rates and increased postoperative complications. [14,15] In our study, we defined geriatric patients as those aged ≥60 years, utilizing the same criteria for classification.…”
Section: Study Description and Definitionsmentioning
confidence: 99%
“…[11][12][13] These studies have demonstrated that being >60 years of age is a significant factor independently associated with higher mortality rates and increased postoperative complications. [14,15] In our study, we defined geriatric patients as those aged ≥60 years, utilizing the same criteria for classification.…”
Section: Study Description and Definitionsmentioning
confidence: 99%
“…The conspicuous advantages of DAA may include: (1) cosmetic benefits, such as small incision (including bikini incision), minimally-invasive and tissue-sparing surgery achieved via neuro-muscular interface [17]; (2) fast recovery, as promoted by less blood loss and pain, faster functional recovery in terms of muscle strength, range of motion, gait and early return to weight-bearing activities [4,10]; (3) more favorable outcomes, including reduced dislocation rate and increased likelihood of components being placed into the safe zone [18]. If we further look into the issue, especially when a surgeon's volume of DAA operation is more than 2000 cases, we will find that the advantages of DAA are beyond above-mentioned benefits to include the functional gain in hip-spine complex.…”
Section: Advantages Of Daa In Surgical Decision-makingmentioning
confidence: 99%
“…We also developed several innovative techniques in terms of targeted soft-tissue releasing, leg-length equalization algorithm, and subtrochanteric shortening osteotomy (SSO) [6][7][8]. The results showed superior functional recovery in general and follow-up studies exhibited improvement in gait and hip abduction and flexion muscle strength in particular [9,10]. Furthermore, in the recent two years, we also explored the clinical potential of extensile DAA in 50 cases of partial and total revisions in hip arthroplasty.…”
Section: Introductionmentioning
confidence: 99%